Mood disorder associated with cannabinoid and codeine use: a case - İzci, Filiz and Bozkurt Zincir, Selma and Bilici, Rabia and Semiz, Ümit Başar (Journal of Dependence, 2014)
Addictive substances cause mood disorders, psychotic disorders and behavioral disorders by affecting the Central Nervous System. Cannabis and codeine, a morphine analog, are substances that have addiction potential. Some preparations used to treat common cold may contain codeine as well as acetaminophen and chlorpheniramine. Here we present a case who had been addicted to cannabis for 6 years and later started to abuse high doses of common cold medications containing codeine and started to show symptoms of mood dysorder with psychotic features.